A 14-Year Review of Craniomaxillofacial Gunshot Wounds in a Resource-Limited Setting. Issue 2 (June 2017) - Amole, Olushola; Osunde, Otasowie; Akhiwu, Benjamin; Efunkoya, Akinwale; Omeje, Kelvin; Amole, Taiwo; Iliyasu, Zubairu
This study analyzed the prevalence, clinical characteristics, and management of civilian-type craniomaxillofacial gunshot wounds (CGSWs) seen over a 14-year period in a Northern Nigerian teaching hospital. A retrospective study of all hospital records relating to CGSWs from January 2000 to December 2013 was conducted to determine the prevalence of CGSWs. Information retrieved included site of injury, type of projectile, management protocol, as well as duration of hospitalization. A total of 46 admissions for CGSWs were recorded during the period under review from a total of 2, 228 maxillofacial admissions. This gave a prevalence of 2.1% for CGSWs (95% confidence interval = 1.56–2.81). Sex distribution was 14.3:1 (M:F) with overall mean age of 32.9 ± 8.4 years. Average length of hospitalization was 17.7 (± 15.56) days. Management of CGSWs consisted of emergency care, preliminary intervention, definitive reconstruction, revisions, and rehabilitation. Conclusively, analysis of the yearly incidence of CGSWs showed that the incidence and severity increased within the past 2 years under review (18 cases, 39.13%; χ 2 trend = 7.7, p = 0.006). This period was noted to correspond with heightened violence within the region mostly due to the acts of unknown gunmen and insurgents.